Common mental disorders and associated factors among adults after COVID-19 pandemic in Ethiopia: a systematic review and meta-analysis - Temesgen Gebeyehu Wondmeneh; Zelalem Solomon (BMC Psychiatry)
Abstract Background Global mental health has been threatened by the COVID-19 pandemic, both directly through long-lasting neuropsychiatric disorders that occur during primary infection in affected individuals and indirectly through stressful and disruptive societal changes. Thus, this study determined the pooled prevalence of common mental disorders and associated factors among adults after COVID-19 pandemic in Ethiopia. Methods This systematic review and meta-analysis were conducted using primary published and unpublished studies that were retrieved from various databases. Studies conducted on adults, published in English, and conducted in Ethiopia were included in this review. A standardized data extraction format developed from Excel was used to collect the data. A random effect meta-analysis model was used to estimate the pooled effect size of all included studies at a 95% confidence interval. The heterogeneity was evaluated by Cochran Q test and the I-squared. Funnel plot and egger tests were used to determine publication bias. Results A total of 20 studies were eligible for this systematic review. The pooled prevalence of common mental disorders among adults was 40.44% (95%CI: 31.86–49.02%). Female gender (AOR = 1.88, 95% CI: 1.33–2.44), unemployed (AOR = 2.05, 95% CI: 1.12–2.98), poor social support (AOR = 3.12, 95% CI: 2.08–4.17), substance use (AOR = 2.5, 95% CI: 1.58–3.41), history of mental illness (AOR = 1.73, 95% CI: 1.01–2.44), family history of mental illness (AOR = 2.47, 95% CI: 1.54–3.41), and chronic medical illness (AOR = 1.6, 95%CI:1.02–2.17) were risk factors for common mental disorders. Conclusion In this study, more than one-third of adults were affected by common mental disorders after the onset of the COVID-19 pandemic. This indicated that, in order to reduce the prevalence of common mental disorders, enhancing the provision of mental health services should be improved after the COVID-19 pandemic. Screening for common mental disorders should be given, especially to females, unemployed people, substance users, chronic medically ill people, those with a history of mental illnesses, and those with a family history of mental illness. Strengthening social support during the COVID-19 pandemic is also important. PROSPERO protocol registration The registration ID for this systematic review is CRD42024496826.